‘For in the day that you eat of it, you shall surely die’. The early reception history of the death warning in Genesis 2:17 - Lee, Chris Wonjae (The University of Edinburgh, 2019)
This thesis examines the early Jewish reception of the divine prohibitive command (Gen 2:16-17) in relation to its interpretative association with the introduction of physical death to humanity. The long-time rationale has been that the eating of the tree of the knowledge of good and evil brought sin and death ‘for in the day that you eat of it, you shall surely die’ (Gen 2:17). The thesis begins by examining the meaning of Gen 2:17 in its original context, then tracing its interpretation in subsequent Second Temple Jewish Literature. The study examines the Greek translation of Gen 2:16-17 and its translational elements that expand the possible range of understanding of the prohibition that would not have originated from the Hebrew text of Genesis. The thesis continues with an exegetical analysis of allusions and references to the prohibitive command in the Dead Sea Scrolls, the Book of Ben Sira, 1 Corinthians and Romans. It is argued, firstly, that there are no explicit narrative clues in the HB as to the physical status of Adam and Eve either as immortal or mortal before their disobedience to God’s command in Gen 2:17, and that the death warning itself does not provide textual support for the understanding of the death warning in the sense of becoming mortal. It is also argued that Paul’s explicit attribution of death to the disobedience of Adam and Eve (1 Cor 15:21-22; Rom 5:12) finds its earlier traces in the course of interpretation of the aforementioned literature: 1) clarification of the meaning of the death warning, i.e. death in the sense of becoming ‘mortal’ and death due to the violation of the command as applicable not only to Adam, but also to Eve and other human beings; 2) reinforcement of the presumptive association between the death warning and the introduction of death to humanity.
Keywords: early Jewish thought; Genesis 2:17; Second Temple Literature; Exegesis; Book of Ben Sira; 1 Corinthians; Romans; death warning; disobedience of Adam and Eve; mortality